Frequency of Fibromyalgia in Patients with Chronic Hepatitis C Virus Infection and Its Relationship with Vitamin D Levels and Quality of Life - Havva Talay Calis; Fatma Gul Ulku Demir; Ulas Serkan Topaloglu; Hatice Sayan; Deniz Kamalak Guzel; Emel Guler; Fatma Samli; Caglar Karabas; Serap Tomruk Sutbeyaz; Hatice Kayis Topaloglu (Haseki Tıp Bülteni)
Aim: The literature on the effects of the fibromyalgia syndrome (FMS) association with hepatitis C virus (HCV) on quality of life and vitamin D levels is limited. We aimed to evaluate the frequency of fibromyalgia in patients with chronic hepatitis C virus (HCV) and also to analyze the relationship between the presence of fibromyalgia and vitamin D parameters. Methods: This controlled, cross-sectional study of 123 participants (72 patients with HCV and 51 in the control group) was conducted in a tertiary hospital. The study enrolled age- gender and BMI-matched control groups. Patients were diagnosed with fibromyalgia and arthritis as per the 2010 American College of Rheumatology diagnostic criteria. Fibromyalgia Impact Questionnaire (FIQ), Nottingham Health Profile (NHP) and the level of vitamin D were performed in all patients. Results: The presence of fibromyalgia, the level of vitamin D and the score of FIQ were statistically different between HCV (+) and control groups. The score of social isolation was higher in the HCV (+) group, whereas all other scores were similar in both groups according to the NHP scale. Based on the presence or absence of fibromyalgia, all scores of FIQ and NHP scales were higher in a subgroup with fibromyalgia. This study documented a prevalence of 56.9% of FMS in patients with HCV (+) in comparison to the control group Conclusion: This study documented a high prevalence of 56.9% of FMS in patients with HCV (+) in comparison to the control group. While emphasizing raising awareness of fibromyalgia, its relationship with HCV, vitamin D, quality of life, age, gender, BMI, and tender points was revealed via regression analysis.